Konsep dan pelaksanaan wakaf di Malaysia (Kuala Lumpur Institut Kefahaman Islam Malaysia, 1999)
Essays on the concept and implementation of waqf in Malaysia; papers of a seminar.
Includes bibliographical references and index.
Keywords: Islam and state -- Malaysia; Islamic law -- Malaysia; Waqf -- Malaysia